Der metafiktionale Roman Untersuchungen zur Prosa Konstantin Vaginovs - Bohnet, Christine (Slavistische Beitraege, 1998)
The focus of this work is the prose of the Leningrad late avant-gardist Konstantin Vaginov (1899-1934). The aim is to develop a terminology and a concept by means of which the special type of text of the late avant-garde meta-novel Vaginovian style can be adequately described.